Public health and the use of medicinal plants as integrative practices (Research, Society and Development, 2022)
Objective: To address the importance of medicinal plants for public management, highlighting that medicinal plants are becoming increasingly a good option for public health in the face of health-related use for its effectiveness and cost. Methods: A literature review was carried out in an exploratory descriptive way with a qualitative approach. Results: There are many reports of benefits from the use of medicinal plants, being used by much of the population both in Brazil and worldwide, as well as in developing and developed countries, but some reasons end up worrying, because the product needs to be used correctly, and a major concern is the exaggerated self-medication, associated with allopathic medications, without communication to the doctor, and the lack of knowledge about the medicinal and toxic effects of plants. Final considerations: When we talk specifically about values, the medicinal plants are inserted in the low cost and accessibility, it is easy to prepare a home remedy made with some medicinal plants found in the garden or even already prepared in the form of infusions and bottles that are bought in fairs, as well as in the form of extracts and essential oils, being many times the only economical way to have medication, for not having access to other forms.